Plant-based skin lightening agents: a review - Mohd Hanif, Nadzirah; Mohammed Ahmed, Abdul Kareem; Khalid, Kamarul Ariffin; Ab. Hadi, Hazrina (Society of Pharmacognosy and Phytochemistry, 2020)
Hyperpigmentation is a skin disorder that occurs widely in the human population in which darkened patches or spots appear on the skin. Cosmetic products containing natural skin lightening agents are regarded as a safe alternative and effective approach to this hyperpigmentation problem. The review paper aims to discuss on some potential plant species with skin lightening properties by focusing on the presence of responsible bioactive compounds and their specific mechanisms of action in minimizing melanin production in hyperpigmentation problem. The finding shows that different bioactive compounds have various modes of action on melanin biosynthesis pathway including tyrosinase inhibition, melanosomes transfer inhibition, anti-oxidant and anti-inflammatory activities. Some plants with skin lightening activity contain several bioactive compounds which contribute to an enhancement of skin lightening effects and inhibition of hyperpigmentation. In conclusion, the screening of potential skin lightening ingredients from natural sources is very crucial process before formulation development for an effective skin lightening product.